The role of the habituation curriculum in encouraging the improvement of students’ social skills in the digital era - Kartika Dwi Hartini; Mustajab Mustajab; Mas’ud Mas’ud (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study examines the impact of the habituation curriculum on enhancing students’ social skills in the digital era. With the increasing reliance on digital technology, students face challenges in developing interpersonal communication and empathy. Therefore, examining how a habituation-based curriculum can bridge this gap is essential. The primary aim of this research is to evaluate the effectiveness of the habituation curriculum in promoting more effective social interactions among students within the context of modern educational environments. The study employs a mixed-methods approach, combining qualitative and quantitative data collection techniques. To gain insight into the impact of the habituation curriculum, researchers conducted surveys and interviews with educators to gather their perspectives on the topic. The findings indicate that habituation practices significantly improve students’ ability to engage in meaningful offline and online social interactions. The research emphasizes the importance of incorporating habituation strategies into the curriculum to address the challenges posed by digital communication platforms. It supports the development of well-rounded, socially competent individuals. This study offers valuable implications for educators seeking to adapt teaching methods to contemporary needs. Abstrak Penelitian ini mengeksplorasi peran kurikulum habituasi dalam meningkatkan keterampilan sosial siswa di era digital. Dengan semakin meningkatnya ketergantungan pada teknologi digital, siswa menghadapi tantangan dalam mengembangkan komunikasi interpersonal dan empati. Oleh karena itu, penting untuk meneliti bagaimana kurikulum berbasis habituasi dapat menjembatani kesenjangan ini. Tujuan utama dari penelitian ini adalah untuk menilai efektivitas kurikulum habituasi dalam mendorong interaksi sosial yang lebih baik di kalangan siswa dalam konteks lingkungan pendidikan modern. Penelitian ini menggunakan pendekatan metode campuran, menggabungkan teknik pengumpulan data kualitatif dan kuantitatif. Untuk menggali wawasan mengenai dampak kurikulum habituasi, peneliti melakukan survei dan wawancara kepada pendidik. Temuan penelitian menunjukkan bahwa praktik habituasi secara signifikan meningkatkan kemampuan siswa untuk terlibat dalam interaksi sosial yang bermakna, baik secara offline maupun online. Penelitian ini menyoroti pentingnya mengintegrasikan strategi habituasi dalam kurikulum untuk mengatasi tantangan yang ditimbulkan oleh platform komunikasi digital dan mendukung pengembangan individu yang terampil secara sosial. Penelitian ini memberikan implikasi yang berharga bagi pendidik yang berusaha menyesuaikan metode pengajaran dengan kebutuhan kontemporer. Kata Kunci: era digital; kurikulum habituasi; keterampilan sosial